Fast linear electro-optic effect in a centrosymmetric semiconductor. Issue 1 (December 2018) - Berciano, Mathias; Marcaud, Guillaume; Damas, Pedro; Roux, Xavier; Crozat, Paul; Alonso Ramos, Carlos; Pérez Galacho, Diego; Benedikovic, Daniel; Marris-Morini, Delphine; Cassan, Eric; Vivien, Laurent
Abstract Silicon photonics, considered as a major photonic platform for optical communications in data centers, is today also developed for others applications including quantum photonics and sensing. Advanced silicon functionalities based on optical nonlinearities are then required. As the presence of inversion symmetry in the Si crystal structure prevents the exploitation of second-order optical nonlinearities, the generation of strain gradients in Si by a stressed material can be considered. However, due to the semiconductor nature of silicon with the presence of carriers, no clear evidence of second-order nonlinearities have been reported yet. Here we report an experimental demonstration of high-speed Pockels effect in silicon waveguides at 1550 nm. Additionally, a theoretical model is developed to describe its frequency behavior. A second-order nonlinear susceptibility χ _xxy^(2) χ x x y ( 2 ) of −1.8 ± 0.2 pm V−1 is then experimentally determined. These results pave the way for the development of fast linear electro-optic effect for advanced silicon photonics devices. Silicon holds the promise of hosting future photonic circuitries, but its centrosymmetric crystal structure precludes the exploitation of beneficial second-order nonlinearities. The authors demonstrate that strain fields can enable such nonlinearities in silicon, showing high-speed optical modulation through the so-called Pockels effect.